An Analysis of Numeracy Skills in The Education Report of SDN 184 Pekanbaru - Aznel, Khofifah; Natuna , Daeng Ayub; Makhdalena , Makhdalena (CV. Tripe Konsultan, 2024)
This study examines the gap between numeracy scores presented in the national Education Report and the actual assessment results of students at SDN 184 Pekanbaru. The primary objective of this research is to analyze the extent to which macro-level national data aligns with the actual numeracy achievements of students in the classroom. The research subjects consisted of 20 fifth-grade students selected using purposive sampling techniques based on the diversity of their academic achievements. This study employed a qualitative descriptive approach with data collection methods including the analysis of the 2025 Education Report document and field-based numeracy assessments developed to measure students’ numeracy competencies. The numeracy domains analyzed include number, algebra, geometry, as well as data and uncertainty. The findings revealed that the numeracy score in the Education Report was 53.33%, generally indicating the attainment of minimum competency. However, the students' actual assessment results showed an average score of only 46.70%, indicating a performance gap. Students tended to perform better in the number and geometry domains but faced significant challenges in algebraic reasoning and data interpretation. These findings underscore the importance of cross-verifying national report data with classroom assessments to obtain a more comprehensive understanding of learning outcomes. The study recommends that schools conduct regular and contextual evaluations of numeracy learning and implement teaching strategies better aligned with students’ cognitive readiness and real-life experiences. The results offer practical implications for instructional planning, learning design, and the implementation of targeted numeracy interventions in primary school environments.